“Satellite pedicle screws” - A novel technique of pedicle screw insertion in obese patients undergoing lumbar fusion - Rishi M. Kanna; Ajoy P. Shetty; S. Rajasekaran (World Neurosurgery: X, 2023)
The presence of thick sub-cutaneous fat and bulky paraspinal musculature mandates extensive surgical dissection in obese patients undergoing open Transforaminal lumbar interbody fusion surgery. Securing a ‘converging’ pedicle screw trajectory becomes difficult by the counterforces of the erector spinae muscles and thick sub-cutaneous fat in obese patients, especially at the L5-S1 level. We describe the use of a limited standard posterior midline exposure and a separate, far lateral ‘satellite’ incision to insert pedicle screws in an optimal trajectory in obese patients. Through proper pre-operative planning of the axial and sagittal MRI, the appropriate entry site is determined which is executed intra-operatively to insert pedicle screws freehand. Through a single 1.5 cm incision, both L5-S1 screws were inserted. Fourteen obese patients (mean BMI was 30.5 ± 1.1) received 56 satellite pedicle screws for TLIF at L5-S1 level. The mean age was 48.3 ± 9.7 years. The mean blood loss was 244.8 ± 114 ml and the mean operative time was 126.7 ± 82.8 min. In all patients, the screws were inserted as per pre-operative planning without any difficulties. All wounds healed well without wound complications. There were no screw related complications, and in the antero-posterior and lateral radiographs, there were no screw breaches. Satellite free-hand pedicle screws are safe and easily reproducible. They enable limited dissection of the main surgical wound and well-medialised converging pedicle screws in obese patients.